2013
DOI: 10.1248/bpb.b12-00774
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Hyperthermia Promotes the Sensitivity of MCF-7 Human Breast Cancer Cells to Paclitaxel

Abstract: As a physical adjuvant approach in the treatment of solid tumors, regional hyperthermia plays a synergistic role in enhancing the efficacy of simultaneous chemotherapy. Paclitaxel (PTX) is an anti-mitotic taxane drug that is widely used in chemotherapy for the treatment of various human malignancies such as lung, ovarian, breast, and head and neck cancers. Since the possibility that hyperthermia can enhance the antitumor effects of PTX has not yet been investigated, the present study was designed to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…Analysis of cell cycle revealed increased presence of HT29 cells in G 2 /M phase after heat shock application, while combination of hyperthermia with auraptene resulted in considerable accumulation of cells in sub G 1 /G 1 phase. In consistence with our findings, G 2 /M phase arrest was reported after hyperthermia in several cell types such as liver, lung, breast and renal cancer cells (Qi et al 2015;Zhao et al 2015;Yan et al 2014;Lin et al 2013). Same as present results, previous studies have also indicated growth controlling effects of auraptene on breast and gastric carcinoma cells by cell cycle arrest in sub G 1 (Mousavi et al 2015, Moon et al 2015 and G 0 -G 1 phases (de Medina et al 2010;Krishnan et al 2009).…”
Section: R a F Tsupporting
confidence: 91%
“…Analysis of cell cycle revealed increased presence of HT29 cells in G 2 /M phase after heat shock application, while combination of hyperthermia with auraptene resulted in considerable accumulation of cells in sub G 1 /G 1 phase. In consistence with our findings, G 2 /M phase arrest was reported after hyperthermia in several cell types such as liver, lung, breast and renal cancer cells (Qi et al 2015;Zhao et al 2015;Yan et al 2014;Lin et al 2013). Same as present results, previous studies have also indicated growth controlling effects of auraptene on breast and gastric carcinoma cells by cell cycle arrest in sub G 1 (Mousavi et al 2015, Moon et al 2015 and G 0 -G 1 phases (de Medina et al 2010;Krishnan et al 2009).…”
Section: R a F Tsupporting
confidence: 91%
“…31,37,39,50,51 Both in vitro and in vivo studies proved that this combination induced a "thermal enhancement" for PTX cytotoxicity. 31,50,51 In current clinical trials, PTX is administered with hyperthermic perfusion for the treatment of ovarian and lung cancers and gastrointestinal neoplasms (http://www.clinicaltrial.gov).…”
Section: Discussionmentioning
confidence: 95%
“…Physiological hyperthermia (39.5-45 °C) has been used as enhancer of radiotherapy and of many chemotherapeutic agents, 30 including PTX, [31][32][33] with limited toxicity to normal tissues. 34 Hyperthermia is mainly applied locally, regionally, interstitially, or to the whole body according to the tumor type, stage, depth, localization, and presence of spread metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HT is reported to be a good strategy for cancer both by itself [1] and in conjunction with radiotherapy or chemotherapy [38, 39]. In addition, it is now considered a potential tool for treating cancer after surgery, radiotherapy, and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%